Exchanging money for love? A regional analysis of EU cohesion policy on euroscepticism - Michael Bayerlein; Matthias Diermeier (Kiel Institute for the World Economy (IfW Kiel), 2022)
In the past, the European Union seems to have been able to tame Euroscepticism through regional 'convergence' funding. After the Eastern enlargement of the Union, however, this relationship needs to be put to the test. Not only have the new member states become the main recipients of EU funding, Eastern Europe has also changed from once being the most integration-friendly region to displaying the most integration-hostile attitudes in the EU. Motivated by this empirical puzzle, we revisit the relationship between structural 'convergence' funding and Euroscepticism and ask where - if at all - is the EU's convergence spending still able to tame Euroscepticism. Most surprisingly, correlation analyses reveal that between 2006 and 2018 larger regional subsidies go along with increasing opposition to EU integration. We can rebut this counterintuitive finding by a Diff-in-Diff approach that reveals an increasing Euroscepticism in Eastern European regions between 2006 and 2014. Nevertheless, also these more advanced models fail to establish a positive relationship between regional funding eligibility and pro-integrationist attitudes. Finally, fuzzy RDD models exploit the funding assignment rule and corroborate that the EU is no longer able to pacify integration-critical regions by their simply increasing 'convergence' funding. Nevertheless, the EU has won support in Eastern Europe where EU investments are perceived (positively). In designing a strategy to win back support for EU integration, Brussels does not need more fiscal capacity but rather has to design 'convergence' funding that is visible as well as clearly attributable to its donor.
Keywords: D72; F14; H11; I38; 330; Euroscepticism; cohesion policy; EU transfers; methodology; regional analysis